The Role Protein Sonic Hedgehog in Carcinoma Basal Cell - Yulia Farida Yahya; Radema Maradom; Hari Darmawan; Theresia L. Toruan; Ika Kartika (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TIntroduction: Basal cell carcinoma (KSB) is a non-melanoma skin cancer (KKNM),which is most commonly found compared to other skin cancers. KSB originates fromstem cells in the bulk of hair follicles or inter-follicular epidermis, through the Sonichadgehog (SHH) activation pathway, an increase in Sonic hadgehog (SHH) proteinexpression, involving Patches protein (PTCH), smothened protein (SMO), in the formof increased protein transcription activation Glia (GLI) in the nucleus, binds to DNAto initiate tumor-aggressive growth and tissue. Objective: to determine therelationship between Sonic hadgehog (SHH) expression and non-aggressive andaggressive basal cell carcinoma. Methods: The study was carried out in anobservational laboratory with 35 primary KSB patients, the tissue was taken usingelliptic biopsy technique, made paraffin block specimens for histopathologicalexamination of the subtype of KSB consisting of 20 non-aggressive KSB patients,namely nodular and superficial KSB; 15 patients with aggressive KSB werepigmented KSB; Infiltrates KSB, micronodular KSB, metypical KSB (basosquamousKSB) and SHH immunohistochemical (CPI) examination using SHH antibodies, inthe Anatomy Pathology section, FK Unsri / RSMH Palembang. The characteristics ofKSB patients were recorded, namely sex, age, occupation based on the length ofexposure to BC, namely exposure <3 hours / day, exposure 3-6 hours / day,exposure ≥ 6 hours / day. The data were processed using the Statistical AnalysisSoftware Package (SPSS) version 20.0 (IBM Corporation), tested with Pearsoncorrelation test and chi square test and presented in the form of diagrams, andnarrative tables. Results: Pearson's test showed a significant correlation betweenthe clinical features of KSB and the histopathologic features of non-aggressive andaggressive types of KSB (p 0.020), there was a significant relationship between thesubtypes of histopathologic features of KSB with non-aggressive and aggressivetypes of KSB (p 0.000), there was a significant relationship between strong SHHexpression and BCC aggressive compared to non-aggressive KSB, p 0.000 (p <05α),and r = 732 Conclusion: There is a relationship between SHH expression and KSBaggressiveness. The increase in strong SHH expression shows the aggressiveness ofKSB, SHH expression can be used as a biological gene target both as a prognosticindicator and can be used as a target for treatment of aggressive KSB, especially inthe elderly.